West African Economic and Monetary Union : Common Policies of Member Countries-Press Release; Staff Report; and Statement by the Executive Director for the West African Economic and Monetary Union. (IMF Staff Country Reports; Country Report ;, 2017)
This paper examines common policies supporting reform programs in member countries of the West African Economic and Monetary Union (WAEMU). Economic activity in WAEMU has remained strong but vulnerabilities have increased. Real GDP growth is estimated to have reached 6.2 percent in 2016, underpinned by robust and resilient domestic demand. Inflation remained subdued, at about 0.4 percent on average in 2016 owing to continued solid agricultural production and low oil prices. Preliminary data suggest an overall fiscal deficit of 4.5 percent of GDP in 2016, higher than initially planned. The outlook remains positive provided there is continued macroeconomic stability and resolve to improve the business environment and promote private investment.